STUDENTS’ ABILITY IN READING COMPREHENSION - Putri, Maharani (Ensiklopedia Sosial Review, 2019)
This research was aimed to find out the students’ ability in reading comprehension for second year of SMK YPM Zain Pauh Kambar Padang Pariaman in 2013/2014 academic year. This research was quantitative approach. The sample of this research was 62 students who were taken by using random sampling technique. The data was collected by reading comprehension test. The research findings show that students’ reading comprehension still in low category. It was supported from the data that only 16.13% who got high score and 29.03% who got low score.